Examining the Relationship between Community Participation and Program Outcomes in a Metaevaluation - Apollo M Nkwake; Holta Trandafili; Joel Hughey (Journal of MultiDisciplinary Evaluation)
Background: The salience of stakeholder participation in community development is not disputed. However, there is a paucity of evidence that clearly links participation with program outcomes.